Selected aspects of quality of life in parents of children with bronchial asthma - Trojanowska, Alina; Emeryk, Andrzej (Polish Journal of Public Health, 2009)
Introduction. Bronchial asthma is the most frequent chronic childhood disease of increasing morbidity. In the light of recent knowledge asthma requires complex treatment and involves child’s family in long-term therapeutic and educational process. All burden resulting from child’s chronic condition and its treatment can impair the activity of the whole family. Aim. The purpose of study was to evaluate the quality of life of the parents whose children suffer from bronchial asthma. Material and methods. The investigation covered 100 parents with children suffering from chronic bronchial asthma and undergoing ambulant treatment at the Pulmonological Out-patient Department, Children Clinical Hospital in Lublin. The research tools used in the study were: PAQLQ questionnaire, a questionnaire created for the purpose of study and analysis of medical records. Results. According to 90% parents, child’s disease and its treatment limit their life activity. Child’s asthma was responsible for impaired emotions in 98% parents. Statistic analysis confirmed significant correlation between the degree of asthma severity and parents’ QL (p=0.004). Over half of the respondents (59%) observed annoying side effects believed to be associated with the type of treatment. Statistic analysis found significant infl uence of side effects of the therapy on the parents’ QL (p=0.001). The study also analyzed the role of financial expenses to cover the cost of BA treatment on the parents’ QL. Statistic analysis revealed significant infl uence of the increased value of that parameter on the parents’ QL (p=0.026). The analysis of correlation revealed significant, slight though, positive correlation between the duration of treatment by a specialist and parents’ QL (r=0.203, p<0.05). Conclusions. Burden due to child’s chronic disease decreases considerably parents’ QL, especially in the area of emotions. Therapy of asthmatic child should be extended by psycho-educational activities addressed at his/her family.